Student Learning Motivation in Online Learning in the Covid-19 Period: Motivasi Belajar Mahasiswa Pada Pembelajaran Daring di Masa Covid - 19 - Munir, Muhammad; Sholehah, Hijriati (Universitas Muhammadiyah Sidoarjo, 2021)
Motivation is a change in energy in a person's personality, characterized by the emergence of feelings (affective) and reactions to achieve goals. Learning is observing, reading, imitating, trying something yourself, listening, following directions. The implementation of online learning is not something new for students. Still, online learning is not as effective as face-to-face learning because online learning is not too free to express problems; this is caused by factors such as internet signals, cellphones / or similar tools which can be used for the internet, and others. This has an impact on student learning motivation. This research aims to find out students' learning motivation in online/online learning during the covid 19 period. The research used in this study is survey research; this study aims to describe/explain events or circumstances. Based on the results of data analysis, students' learning motivation in online learning is the highest or equal to 70% of the average ideal value. This shows that students' learning motivation is less than or equal to 70%. It can be stated that covid 19 has an impact on students' learning motivation.